Case Report: Cervical cancer masquerading as ovarian tumor: diagnostic challenges in a case with severe pyometra-pyocolpos complex - Xie, Chaoping; Liu, Hongcen; Huang, Daxia; Zhao, Ganmei; Qiu, Min; Liu, Yong; Mao, Dongwei (Frontiers in Oncology, 2025)
Introduction and importanceEarly-stage cervical cancer, which is often asymptomatic, presents considerable diagnostic difficulties when accompanied by vaginal adhesions that conceal malignant lesions. In this report, we describe an exceptionally rare case of cervical cancer complicated by extensive pyometra and pyocolpos, highlighting key diagnostic challenges and evidence-based treatment approaches.Case presentationA 61-year-old postmenopausal woman presented with abdominal distension and pain. Initial imaging, including ultrasound and CT, suggested an ovarian tumor. However, contrast-enhanced MRI identified a pyometra and pyocolpos complex, with malignant cytology detected in the drained fluid. Diagnostic exploratory laparotomy was necessitated due to extensive pyometra and pyocolpos precluding adequate diagnostic biopsy, with final histopathological confirmation of stage IIA1 squamous cell carcinoma of the cervix (FIGO 2018 criteria). Following the cervical cancer diagnosis, the patient underwent radical hysterectomy with bilateral salpingo-oophorectomy in late May 202, and received adjuvant radiotherapy post-discharge as further treatment.Clinical discussionThe coexistence of cervical cancer complicated by extensive pyometra and pyocolpos is a rare clinical condition that requires a comprehensive multidisciplinary diagnostic approach. For such complex presentations, a tripartite protocol—combining imaging continuity assessment, post-drainage cytomorphologic analysis, and histopathologic verification—is essential to circumvent diagnostic delays and sampling errors.Conclusion①Postmenopausal pyometra cannot be excluded as a complication of gynecologic malignancies. High-grade squamous intraepithelial lesion (HSIL) and squamous cell carcinoma antigen (SCC) can directly extend proximally into the uterus. The most common clinical manifestations include pyometra and cervical stenosis. Emphasis should be placed on early detection and prevention of this condition. ②Combined human papillomavirus (HPV) testing and ThinPrep cytologic test (TCT) screening improve the detection rate of cervical lesions. However, in this patient, vaginal wall adhesions prevented cervical exposure, resulting in a false-negative finding and increasing the risk of missed diagnosis. ③Elevated serum levels of squamous cell carcinoma antigen (SCC-Ag) warrant heightened clinical vigilance. As a first-line serum biomarker for cervical cancer screening, SCC-Ag elevation may precede the onset of other clinical manifestations in affected patients. ④For cervical carcinomas with limited tumor size (maximal diameter <2 cm), a multimodal diagnostic integration incorporating serum tumor markers (SCC-Ag, CA125), advanced contrast-enhanced imaging (CT/MRI), and diagnostic surgical exploration may be considered. ⑤For early-stage cervical cancer patients complicated by uterovaginal abscess, a staged treatment approach should be adopted. And it’s also essential to balance the priorities of infection control and antitumor therapy.